Zebrafish: A Model to Study and Understand the Diabetic Nephropathy and Other Microvascular Complications of Type 2 Diabetes Mellitus - Charles Sharchil; Amulya Vijay; Vinu Ramachandran; Sambhavi Bhagavatheeswaran; Reena Devarajan; Bhupendra Koul; Dhananjay Yadav; Anandan Balakrishnan (Veterinary Sciences, 2022)
Diabetes mellitus (DM) is a complicated metabolic illness that has had a worldwide impact and placed an unsustainable load on both developed and developing countries’ health care systems. According to the International Diabetes Federation, roughly 537 million individuals had diabetes in 2021, with type 2 diabetes mellitus accounting for the majority of cases (T2DM). T2DM is a chronic illness defined by insufficient insulin production from pancreatic islet cells. T2DM generates various micro and macrovascular problems, with diabetic nephropathy (DN) being one of the most serious microvascular consequences, and which can lead to end-stage renal disease. The zebrafish (Danio rerio) has set the way for its future as a disease model organism. As numerous essential developmental processes, such as glucose metabolism and reactive metabolite production pathways, have been identified in zebrafish that are comparable to those seen in humans, it is a good model for studying diabetes and its consequences. It also has many benefits over other vertebrate models, including the permeability of its embryos to small compounds, disease-driven therapeutic target selection, in vivo validation, and deconstruction of biological networks. The organism can also be utilized to investigate and understand the genetic abnormalities linked to the onset of diabetes problems. Zebrafish may be used to examine and visualize the growth, morphology, and function of organs under normal physiological and diabetic settings. The zebrafish has become one of the most useful models for studying DN, especially when combined with genetic alterations and/or mutant or transgenic fish lines. The significant advancements of CRISPR and next-generation sequencing technology for disease modelling in zebrafish, as well as developments in molecular and nano technologies, have advanced the understanding of the molecular mechanisms of several human diseases, including DN. In this review, we emphasize the physiological and pathological processes relating to microvascular problems in zebrafish, as well as the many experimental zebrafish models used to research DN, and the DN-related outcomes and mechanisms observed in zebrafish.